(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND The Kilombero and Ulanga Antiretroviral Cohort (KIULARCO) is a single-site, open and ongoing prospective cohort of people living with human immunodeficiency virus (PLWHIV) established in 2005 at the Chronic Diseases Clinic of Ifakara (CDCI), within the Saint Francis Referral Hospital (SFRH) in Ifakara, Tanzania. The objectives of KIULARCO are to (i) provide patient and cohort-level information on the outcomes of HIV treatment; (ii) provide cohort-level information on opportunistic infections and comorbidities; (iii) evaluate aspects of human immunodeficiency virus (HIV) care and treatment that have national or international policy relevance; (iv) provide a platform for studies on improving HIV care and treatment in sub-Saharan Africa; and (v) contribute to generating local capacity to deal with the challenges posed by the HIV/AIDS pandemic in this region. Moreover, KIULARCO may serve as a model for other healthcare settings in rural sub-Saharan Africa. METHODS Since 2005, all patients diagnosed with HIV at the Saint Francis Referral Hospital are invited to participate in the cohort, including non-pregnant adults, pregnant women, adolescents, children and infants. The information collected includes demographics, baseline and follow-up clinical data, laboratory data, medication history, drug toxicities, diagnoses and outcomes. Real-time data are captured during the patient encounter through an electronic medical record system that allowed transition to a paperless clinic in 2013. In addition, KIULARCO is associated with a biobank of cryopreserved plasma samples and cell pellets collected from all participants before and at different time-points during antiretroviral treatment. RESULTS Up to the end of 2016, 12 185 PLWHIV have been seen at the CDCI; 9218 (76%) of whom have been enrolled into KIULARCO and 6965 (76%) of these have received ART from the clinic. Patients on ART attend at least every 3 months, with laboratory monitoring every 6 months. KIULARCO data have been used to generate relevant information regarding ART outcomes, opportunistic infections, non-AIDS comorbidities, prevention of mother-to-child transmission of HIV, paediatric HIV, and mortality and retention in care. Requests for collaborations on analyses can be submitted to the KIULARCO scientific committee. CONCLUSIONS KIULARCO provides a framework for improving the quality of care of people living with HIV in sub-Saharan Africa, to generate relevant information to evaluate ART programmes and to build local capacity to deal with HIV/AIDS. The comprehensiveness of the data collected, together with the biobank spanning over ten years has created a unique research platform in rural sub-Saharan Africa.